The canonical correlation analysis between the fitness of organizational condition and integration possibility: The evidence of configurational approach - Yin-ying Wang; Shang-ping Lin; Ching-han Fang; Shi-hwa Lo (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
In past literature, most studies discussed organizational fit from a single perspective instead of examining the positive and negative effects of high and low organizational fit through a comprehensive and concrete narrative and integrated concept. Furthermore, most studies attempted to explain "how to make integration work", while omitting "why integration is not easily achieved", often resulting in post-mergers and acquisitions (M&A) failure. This study surveyed top managers working for publicly-traded Taiwanese companies which had processed M&A in the past five years. We randomly chose qualifying companies by using secondary data, and then mailed 300 questionnaires to top managers of the respective firms who were directly or indirectly involved in the M&A. The results of this study indicate the possibility of integration project after M&A has been proven. It signifies high organizational fit companies are more likely to implement organizational management than companies with low organizational fit. Second, the relationship between the organizational fit and the integration possibility of organizational management shows a positive correlation. Specifically, the symmetry of power contains a high correlation with four variables of organizational management.
Keywords: G34; 330; Merger and Acquisition; post-merger management; organizational condition fitness; configuration relationship